The effect of complex, playing-style exercises on motivation, throwing skill, and receiving the hoop in rhythmic gymnastics - Muhammad, Ghofran; Ibrahim, Ismail (Journal of Physical Education, 2023)
The multiplicity of learning methods and the diversity of methods used by the teacher have become one of the foundations of effective teaching, in addition to being one of the most important pillars that connect the learner to the goal, which is learning. Play-style learning is one of the learning methods that teachers have turned to in order to achieve the greatest learning outcome, in addition to the fact that it excites the learner and stimulates his motivation and the spirit of competition to reach the goal. Therefore, the researchers chose it to test the effect of combined exercises in the play-style learning style on both motivation and the throwing skill and Islam in the hoop, which The female students face great difficulty in learning how to perform skills or in achieving any achievement in them, in addition to the poor performance of the female students in this activity. The importance of the research is evident in trying to find a method that stimulates the motivation and spirit of competition for female students to advance the scientific and practical level in the activity under research. The researchers used the experimental method to suit it with the nature of the research and its objectives. The research sample consisted of (34) female students from the third stage, with (4) female students for the exploratory experiment and (15) female students for each of the control and experimental groups for female students. Pre-tests were conducted and those who conducted the experiment were Then, conducting post-tests and using appropriate statistical methods after collecting the data for the tests in order to reach the results required to achieve the research objectives. The researchers concluded that exercises combined with the learning-by-play method had a clear impact on improving motivation and increasing their enthusiasm for learning according to this method among the female students. The researchers recommended Using the method of learning through play in the classroom because of its effect on increasing motivation, as well as the necessity of testing more than one method to achieve good skill learning and increase achievement in the activity under study.